Relationship among self‐injury, experiential avoidance, cognitive fusion, anxiety, and depression in Chinese adolescent patients with nonsuicidal self‐injury - Hu, Zhizhong; Yu, Huijuan; Zou, Jingzhi; Zhang, Yanyan; Lu, Zihang; Hu, Maorong (Brain and behavior, 2021)
Objective To explore relationship among self‐injury behavior, experiential avoidance, cognitive fusion, anxiety, and depression in Chinese adolescent patients with nonsuicidal self‐injury (NSSI). Methods Cognitive fusion questionnaire (CFQ), Acceptance and Action Questionnaire—2nd edition (AAQ‐II), adolescent nonsuicidal self‐injury behavior questionnaire (ANSAQ), Hamilton Anxiety Scale (HAMA), and Hamilton Depression Scale (HAMD) were used as research tools to investigate 120 subjects with NSSI and 130 healthy controls. Results The scores of CFQ and AAQ‐II in the NSSI group were significantly higher than those in the healthy control group (p < .001). The results of regression analysis showed that the experiential avoidance score of patients with NSSI could predict the score of self‐injury questionnaire (β = 0.585, p < .001); when predicting anxiety, only CFQ (β = 0.361, p < .001) entered the equation, with an explanatory variation of 12.3%; when predicting depression, CFQ (β = 0.287, p < .01) entered the equation, with an explanatory variation of 7.4%. Conclusion A high level of cognitive fusion and experiential avoidance may be important factors for the maintenance of self‐injury behavior in patients with NSSI. This study investigated the incidence of postoperative delirium in elderly patients after hip fracture surgery, and to identify risk factors for such, as part of developing a risk stratification index (RSI) system to predict a patient's risk of postoperative delirium.